Isolation and Characterization of Malasezzia Species from Dandruff Samples and Determination of its Sensitivity Towards Antifungal Agents (Bangladesh Pharmaceutical Journal, 2019)
Dandruff is a perennial skin condition manifesting as inflammation and physiologic scaling on the scalp. Malassezia species are the part of the skin microflora of humans and the etiological agents of dandruff. Malassezia comprises of lipophilic and non-lipophilic yeasts. At present topical azoles are used for the treatment of dandruff. This study was conducted to isolate and identify the Malassezia spp. from dandruff samples and to determine their responsiveness towards antifungal agents such as fluconazole, ketoconazole, miconazole and nystatin. Malassezia spp. was isolated using selective media and identified by biochemical tests and microscopic examination. Antifungal activities were assessed by the Kirby Bauer method using well diffusion technique. Total fifteen Malassezia spp. including M. furfur, M. pachydermatis, M. sympodialis and M. globosa were identified from twenty five dandruff samples. Among them, M. furfur was most prevalent (66.67%) followed by M. pachydermatis (13.33%), M. sympodialis (13.33%) and M. globosa (6.67%). All strains were sensitive to the antifungal agents but to different extent. Fluconazole and ketoconazole proved to be the most effective agents against these microorganisms.Bangladesh Pharmaceutical Journal 22(2): 146-152, 2019